A luminescent polyoxoniobate lanthanide derivative Eu3(H2O)9[Nb48O138(H2O)6]27− 1. Issue 26 (16th March 2017) - Chen, Shumin; Ma, Pengtao; Luo, Huihui; Wang, Yangyang; Niu, Jingyang; Wang, Jingping
Abstract : An Eu-containing polyoxoniobate (CN3 H6 )7 K3 H17 Eu3 (H2 O)9 Nb48 O138 (H2 O)6 ·40H2 O is obtained under the protection of citric acid, which is a triangular cylindrical entity and displays red emission. Abstract : A europium-containing isopolyoxoniobate with the formula (CN3 H6 )7 K3 H17 Eu3 (H2 O)9 Nb48 O138 (H2 O)6 ·40H2 O is synthesized under the protection of citric acid. ESI-MS spectra show that the polyoxoanion structural unit Eu3 (H2 O)9 [Nb48 O138 (H2 O)6 ] 27− is intact in aqueous solution. Moreover, its solid-state luminescence displays a red emission with the long lifetime of 258 μs.